2017
DOI: 10.1016/j.meatsci.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR methods for the detection of blown pack spoilage causing Clostridium species; C. estertheticum, C. gasigenes and C. ruminantium

Abstract: A set of real-time PCR methods for the detection of C. estertheticum, C. gasigenes and C. ruminantium, the causative agents of blown pack spoilage (BPS) in vacuum packaged beef, was developed. Robust validation of the sensitivity and specificity was carried out in the three matrices (beef meat drip, wet environmental swabs and dry environmental swabs) as encountered in our testing laboratory and against Clostridium strains (n=76) and non-Clostridium strains (n=36). It was possible to detect 4-5 spores per ml f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Of the 800 samples tested, only 1% (2 silage, 3 air, 2 bedding straw and 1 drinking water) were positive for C. estertheticum using peptone yeast extract glucose starch (PYGS) enrichment followed by conventional PCR (Table 1). In contrast, 10% of samples tested positive by direct qPCR (17 faeces, 15 soil, 9 silage, 8 air, 9 bedding straw, 8 drinking water and 14 puddle water samples), reflecting the increased sensitivity of the qPCR method (Reid et al 2017). Approximately 1% of samples were positive by direct plating including 3 faecal, 1 soil, 1 silage and 4 puddle water samples and counts ranged from 1 to 1Á5 log 10 CFU per g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 800 samples tested, only 1% (2 silage, 3 air, 2 bedding straw and 1 drinking water) were positive for C. estertheticum using peptone yeast extract glucose starch (PYGS) enrichment followed by conventional PCR (Table 1). In contrast, 10% of samples tested positive by direct qPCR (17 faeces, 15 soil, 9 silage, 8 air, 9 bedding straw, 8 drinking water and 14 puddle water samples), reflecting the increased sensitivity of the qPCR method (Reid et al 2017). Approximately 1% of samples were positive by direct plating including 3 faecal, 1 soil, 1 silage and 4 puddle water samples and counts ranged from 1 to 1Á5 log 10 CFU per g.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, 10% of samples tested positive by direct qPCR (17 faeces, 15 soil, 9 silage, 8 air, 9 bedding straw, 8 drinking water and 14 puddle water samples), reflecting the increased sensitivity of the qPCR method (Reid et al . 2017). Approximately 1% of samples were positive by direct plating including 3 faecal, 1 soil, 1 silage and 4 puddle water samples and counts ranged from 1 to 1·5 log 10 CFU per g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C. perfringens is known to be a normal component of intestinal flora, but can cause necrotic enteritis in birds when intestinal dysbiosis occurs [27]. C. ruminantium is reported to contribute to rumen fermentation in cattle and it is also a food-spoiling bacterium, but it has not been directly linked to animal diseases [28].…”
Section: Discussionmentioning
confidence: 99%
“…Robust validation of the sensitivity and specificity in three matrices (beef meat drip, wet environmental swabs and dry environmental swabs) as encountered in their testing laboratory and against Clostridium strains (n = 76) and non-Clostridium strains (n = 36) was undertaken. The authors reported successful detection or 4-5 spores per ml for C. estertheticum, 2 spores per ml for C. gasigenes and 8 spores per ml for C. ruminantium, without the need for sample enrichment (Reid et al, 2017). The team's efforts in deriving optimized sensitivity and specificity parameters have translated in the detection of bacterial spores in extremely low numbers.…”
Section: Polymerase Chain Reactionsmentioning
confidence: 99%